Sex Link Black and Rhode Island Red hens with access to grazing: Productivity and behavior - Cruz Bermúdez, Ana (2021)
Introduction. Learning about the productive and behavior indicators of poultry allows optimizing the pasture access system. Objective. Describe performance, pasture management, and behavior of Rhode Island Red (RIR) and Sex Link Black (SLB) hens in a lodging system on a floor with pasture access. Materials and methods. The research took place in Turrialba, in the province of Cartago, between October 2016 and January 2018, with 210 SLB and 180 RIR hens, aged from 13 to 80 weeks. Body weight, uniformity, mortality, discard, and weekly production percentage, hen housed egg production, feed conversion, feed intake, natural behavior, egg weight and egg mass, were obtained. Pasture management in pasture areas, forage availability, leaf/stem ratio, and the behavior of the poultry in the parks were described. Results. Lower production performance of the SLB and RIR were observed when compared to the Isa Brown genetic line, only the weight of the egg was higher for the RIR hens. Food waste was observed in both groups of birds, the main cause of death was the discard of subordinate birds, pecking, and cannibalism. The most commonly observed behaviors were scratching, pecking, and sand baths. When SLB and RIR poultry entered the parks, fodder production of 5033 and 3460 kg MF GM ha-1 was recorded, respectively. A leaf/stem ratio of >1 was obtained, which reflected a higher preference of the hens for the leaves when grazing. Conclusion. In the flat housing system with access to grazing, the assessed birds displayed low production performance, stress from the heat, loss of feathers due to pecking, cannibalism, and food waste. The production system with access to pasture under the conditions studied was not optimal for the hens used.